The elves and the shoemaker - Grimm, Brothers (England Usborne publication, 2004)
Business was booming for the shoemaker and his wife, until a rival seller stole their customers. with only one piece of leather left, the future looked glum. then two elves arrived, on their own secret mission ......
Location: 3A
Keywords: Elves and the shoemaker